Автоматизована система обліку робочого часу співробітників промислового підприємства - Івченков, Б. А. (ХНУРЕ, 2021)
This article describes an automated system designed for teamwork on IT department projects at a manufacturing plant. The program allows you to create tasks and track their performance. The task can be created by the project manager. The structure of the database contains five objects that the client program will work with: users; projects; tasks; mistakes; categories. All information is stored on a single remote server. To access it, a specialized program must be downloaded from the server, which processes requests from customers and sends them the necessary response. The developed program allows the manager to control the progress of the project, and the executors correctly focus their efforts on more important tasks.
Keywords: облік робочого часу; співробітники промислового підприємства; автоматизовані системи